Assessing emissions–mitigation energy policy under integrated supply and demand analysis: the Colombian case. (20th January 2016) - Cardenas, Laura Milena; Franco, Carlos Jaime; Dyner, Isaac
Abstract: The effects of greenhouse gases on climate variation set policy challenges for the energy industry – the largest greenhouse gas contributor globally. In this context, the energy industry is being subjected to reforms focussing on the environment, internalisation of emission costs and the promotion of cleaner technologies. To overcome the challenges posed by the emission of greenhouse gases, governments have implemented mitigation policies in the power supply industries. Most policy instruments include either financial incentives or goals and standards; and these generate impacts on electricity prices and consumer behaviour. This paper models policies' effects on prices and demand, through an integrated demand and supply analysis for the Colombian case. While simulation of carbon taxes shows important reductions of fossil-fuelled power capacity, a feed-in tariff policy promotes clean technologies, though not significantly reducing use of fossil technologies. When applied simultaneously, policy has a greater impact on both emission reductions and the diffusion of clean technologies, while only increasing electricity prices slightly. Even when price-elasticity of demand is low, such policies may have a significant effect on the penetration of renewables and emissions. Furthermore, this structured modelling of policy helps explain how the ultimate intended goal – sustainable emissions reduction – might be achieved. Highlights: This paper assesses policy for emissions mitigation in the Colombian power sector. Carbon taxes and feed-in tariff will contribute to the preservation of low carbon emissions. Low-carbon policy will preserve low emissions in electricity generation.